DUKUNGAN EMOSIONAL DENGAN INTERACTIVE BRIEFING PADA PASIEN DENGAN KONDISI POST PARTUM DAN SUSPEK KANKERPAYUDARA YANG MENJALANI TINDAKAN BIOPSI - Yolanda Erica Nauli; Hartiah Haroen; Hana Rizmadewi Agustina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Cancer is a chronic illness with a long and complex trajectory, beginning from the pre-diagnostic phase, followed by diagnostic procedures such as biopsy, treatment-related side effects, and ongoing uncertainty regarding treatment outcomes. This uncertainty often heightens patient anxiety, particularly during the biopsy phase, when waiting for results can generate psychological distress comparable to the stress experienced upon receiving a cancer diagnosis. Interactive briefing grounded in an Early Palliative Care (EPC) approach plays an important role in supporting patients’ coping processes, especially in preparing them to receive bad news and face future conditions. This case report describes the application of interactive briefing as an EPC approach in Mrs. E, a 40-year-old postpartum woman on her third day following delivery, who was scheduled to undergo a breast biopsy. The intervention involved therapeutic communication and psychosocial support. Findings indicate a reduction in anxiety, improved psychological readiness, and enhanced patient resilience in dealing with her condition.